LIFE AFTER PANDEMIC: NEUROTICISM DAN MENTAL HEALTH PADA PENYINTAS COVID 19 - Muhammad Afif Alhad; Inayah Ulum Mufidah; Hajar Maqshuroh; Florenxe Naully Gloria Panjaitan (Universitas Sahid Surakarta, 2023)
People are now feeling relieved because the pandemic has come to an end but a discussion about mental health is still going on as the pandemic impacts mental health conditions on individuals. Personality traits are believed to be a strong predictor for mental health conditions especially among adult people. One of the personality traits that is prone to anxiety is neuroticism. This research tried to find out whether Covid 19 survivors with the neuroticism personality trait had a tendency to experience anxiety and depression. A total of 120 respondents obtained through purposive sampling participated in this study. Based on the results of the analysis using simple linear regression, it could be concluded that the neuroticism personality trait had a positive correlation with anxiety and depression, which indicated that Covid 19 survivors with high levels of neuroticism had a tendency to experience anxiety and depression. In addition, the results of the analysis also showed that the neuroticism personality trait explained 56% variance of anxiety and depression. Keywords: Anxiety, Depression, Covid 19 Survivors, Neuroticism